1988
DOI: 10.1172/jci113402
|View full text |Cite
|
Sign up to set email alerts
|

Multiple crm- mutations in familial hypercholesterolemia. Evidence for 13 alleles, including four deletions.

Abstract: The low density lipoprotein (LDL) receptors in fibroblasts from 132 subjects with the clinical syndrome of homozygous familial hypercholesterolemia were analyzed by immunoprecipitation with an anti-LDL receptor monoclonal antibody. 16 of the 132 cell strains (12%) synthesized no immunodetectable LDL receptor protein, indicating the presence of two mutant genes that failed to produce cross-reacting material (crm-mutations). DNA and mRNA from 15 of the 16 cram patients, representing 30 crm genes, were available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
2

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 36 publications
0
23
1
2
Order By: Relevance
“…In addition, it may be predicted that the deletion of exons 13 and 14 and the fusion of exon 12 to exon 15 during splicing leads to a frame shift in mRNA and the occurrence of a premature stop codon in exon 15. 16 A shorter mRNA was documented in the homozygous FH patient reported by Hobbs et al 17 In proband FH-29, we were unable to detect the abnormal mRNA species, presumably because the latter was present in a very low concentration. This is not surprising, as several recent reports have demonstrated that mutations affecting mRNA translation (e.g., nonsense mutations) are often associated with a decreased intracellular level of the abnormal mRNA.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…In addition, it may be predicted that the deletion of exons 13 and 14 and the fusion of exon 12 to exon 15 during splicing leads to a frame shift in mRNA and the occurrence of a premature stop codon in exon 15. 16 A shorter mRNA was documented in the homozygous FH patient reported by Hobbs et al 17 In proband FH-29, we were unable to detect the abnormal mRNA species, presumably because the latter was present in a very low concentration. This is not surprising, as several recent reports have demonstrated that mutations affecting mRNA translation (e.g., nonsense mutations) are often associated with a decreased intracellular level of the abnormal mRNA.…”
Section: Discussioncontrasting
confidence: 46%
“…When this study was repeated using a probe complementary to exons [15][16][17] ure 3D), Bgl II, EcoRl, and EcoRV (data not shown) confirmed the presence of a larger fragment; the digestions with Kpn I, Stu I ( Figure 3E), Nco I, and Pvu II (data not shown) revealed the presence of the additional 5.5-kb fragment. These data indicated that the 5.5-kb abnormal fragments contained sequences that were specifically recognized by the exon 15-17 probe.…”
Section: Proband Fh-30mentioning
confidence: 73%
See 1 more Smart Citation
“…Haplotype analysis of the LDL receptor gene using 10 restriction fragment length polymorphic sites (18) suggested that TT was homozygous for the mutant LDL receptor allele (data not shown). We then used the recently described gene-amplification technique (8) to selectively amplify and sequence exon 2 of the LDL receptor gene, and we determined the nucleotide sequence of the amplified DNA by the Maxam-Gilbert technique (17).…”
Section: Discussionmentioning
confidence: 99%
“…Os pacientes podem ser receptor negativos, expressando pouca ou nenhuma atividade do receptor de LDL, ou receptor defeituoso, levando à expressão de isotipos de LDLR com afinidade reduzida para LDL na superfície dos hepatócitos [42][43][44][45][46][47] .…”
Section: Diagnóstico Genético Da Hipercolesterolemia Familiarunclassified